Enhancing River Monitoring Embedded System using Time Redundancy Fault Tolerance to Resolve Transient Sensor Fault - Mochammad Hannats Hanafi Ichsan; Muhammad Adinura Julian Habibie; Wijaya Kurniawan (Journal of Information Technology and Computer Science, 2023)
Reading data from sensors in the context of the Internet of Things (IoT) is one of the main parameters of a high-reliability system. Data reading by sensors is prone to errors due to various variables that the problem cannot accommodate. One method to overcome this problem is the time redundancy algorithm, where the sensor takes data and its best value several times. In this study, the sensors used to calculate the water levels are ultrasonic sensors and resistance. At the river monitoring point, data is sent using the UDP (User Datagram Protocol) protocol that previous studies have used. This research has been done as a prototype with a maximum distance between sensor nodes of one meter. The results of sending data using UDP were successful, with an average delay of 3293 microseconds. And the ultrasonic sensor that has been tested based on transient fault against time redundancy has an accuracy of 94.5% based on a sampling delay of 1000ms.